2016
DOI: 10.1158/1535-7163.mct-16-0207
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Bifunctional Major Histocompatibility Class I Antibody Fusion Molecules to Redirect CD8 T Cells

Abstract: Bifunctional antibody fusion proteins engaging effector T cells for targeted elimination of tumor cells via CD3 binding have shown efficacy in both preclinical and clinical studies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…Postinfection, these CD8 + T cells become memory-like and get sequestered in peripheral tissue yet remain functional [ 104 ]. These antigen-experienced CD8 + T cells can go on to recognize MHC class I—peptide complexes on the surface of target cells [ 105 ]. By coupling an antitumor antibody fragment to an MHC molecule loaded with a viral peptide (i.e., CMV peptide) and coating the tumor with the complex, a tumor can resemble a virally infected cell, thus marking it for destruction by CVM-specific CD8 + T cells ( Figure 4 ) [ 106 108 ].…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Postinfection, these CD8 + T cells become memory-like and get sequestered in peripheral tissue yet remain functional [ 104 ]. These antigen-experienced CD8 + T cells can go on to recognize MHC class I—peptide complexes on the surface of target cells [ 105 ]. By coupling an antitumor antibody fragment to an MHC molecule loaded with a viral peptide (i.e., CMV peptide) and coating the tumor with the complex, a tumor can resemble a virally infected cell, thus marking it for destruction by CVM-specific CD8 + T cells ( Figure 4 ) [ 106 108 ].…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
“…It has now been shown that in order to create a successful complex, one must add the pMHC1 complex to only one of two antibody chains, in particular, the unfused heavy chain with a “knob” mutation in order to produce less side products [ 105 ]. This technology allows for the expression of heterodimeric IgGs with two dissimilar heavy chains [ 105 ].…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
See 3 more Smart Citations